DOI: 10.11606/t.16.2018.tde-26112020-184250
|View full text |Cite
|
Sign up to set email alerts
|

Conforto térmico em espaços urbanos abertos: verificações modelares como aportes à exploração de abordagens.

Abstract: pela paciência, colaboração e convivência. Aos professores, já aposentados pelo referido departamento: Marcia Alucci, Anésia Frota e Fernando Cremonesi pelo apoio, ensinamentos e amizade. Aos demais professores do Departamento de Tecnologia, aos demais da FAUUSP e aos muitos externos -seria impossível nomear todos vocês sem esquecer de alguém -por todas as oportunidades, discussões e contribuições.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
5

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
1
0
5
Order By: Relevance
“…The maximum air temperature was 31.2°C, at 2:00 p.m. A great effort on the part of the density of vegetation is necessary to reduce the air temperature by 1°C. Although it seems small, it is possible to reach more than 10°C in the thermal sensation depending on the exposure to full sun and shade, percentage of the relative air ratio, wind direction/speed, surface temperatures in and around use, among other conditions (Monteiro, 2018), however, one of the high difficulties in afforesting public roads is the presence of aerial wiring (Velasco, Lima & Couto, 2006). Hourly measurements indicated that the asphalt in full Sun had the highest thermal amplitude (40°C), ranging from 25°C at 6:00 a.m. to 65°C at 12:00 p.m., while the same surface, but shaded by nearby trees on sidewalks, did not exceed 34°C, at the same time.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum air temperature was 31.2°C, at 2:00 p.m. A great effort on the part of the density of vegetation is necessary to reduce the air temperature by 1°C. Although it seems small, it is possible to reach more than 10°C in the thermal sensation depending on the exposure to full sun and shade, percentage of the relative air ratio, wind direction/speed, surface temperatures in and around use, among other conditions (Monteiro, 2018), however, one of the high difficulties in afforesting public roads is the presence of aerial wiring (Velasco, Lima & Couto, 2006). Hourly measurements indicated that the asphalt in full Sun had the highest thermal amplitude (40°C), ranging from 25°C at 6:00 a.m. to 65°C at 12:00 p.m., while the same surface, but shaded by nearby trees on sidewalks, did not exceed 34°C, at the same time.…”
Section: Resultsmentioning
confidence: 99%
“…As análises foram realizadas no programa Urban Multi-Scale Environmental Predictor (UMEP, sigla em inglês), uma ferramenta de análise climática com foco na análise de cidades, dentro da plataforma QGIS (LINDBERH et al, 2019)1210. As escalas interpretativas de sensação térmica tomaram por base a calibração do UTCI proposta por Monteiro (2018) para o município de São Paulo. Com os dados obtidos, criou-se o Índice de Conforto Térmico do Pedestre -ICTP, adimensional, que varia de 0 a 1 (Figura 1).…”
Section: Avaliação Do Conforto Térmico Do Pedestreunclassified
“…Já nos espaços abertos as variáveis ambientais são também passíveis de condicionamento, mas o controle é substancialmente menor, devido à ausência, parcial ou total, de confinamento (HÖPPE, 2002). À especificidade de ausência de confinamento ambiental, acrescentam-se outras dos ambientes externos, como as atividades realizadas e as diferentes expectativas e tolerâncias dos usuários (MONTEIRO, 2018).…”
Section: Introductionunclassified
“…Observa-se, inclusive, que alguns trabalhos de maior abrangência, como por exemplo os de Nikolopoulou (2004), avaliam diferentes ambiências, verificando questões térmicas, sonoras e luminosas em espaços abertos sem, contudo, correlacioná-las. Tem-se ainda trabalhos brasileiros, como o de Spignardi e Monteiro (2018), que aponta a relação entre variáveis microclimáticas e de mobilidade urbana, ou o de Monteiro (2018), que verificou a influência de alguns aspectos acústicos na percepção térmica em espaços urbanos abertos, explorando as ambiências térmica e acústica por meio de um modelo participativo de aquisição de repostas (MONTEIRO et al, 2017).…”
Section: Introductionunclassified